2022
DOI: 10.3389/fped.2022.805466
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Functional Gastrointestinal Disorders in Pediatric Age: A Narrative Review

Abstract: Assessment and management of pain are essential components of pediatric care. Pain in pediatric age is characterized by relevant health and socio-economic consequences due to parental concern, medicalization, and long-term physical and psychological impact in children. Pathophysiological mechanisms of nociception include several pathways in which also individual perception and gut-brain axis seem to be involved. In this narrative review, we analyze the rational and the current clinical findings of probiotic us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Capozza et al have found some specific probiotics showed a significant reduction in crying and fussing compared to placebo in breastfed infants with colic. Besides, in irritable bowel syndrome (IBS), constipation and gastroesophageal reflux, specific strains of probiotics can improve the related symptoms, although current evidence is insufficient to provide any specific recommendation for the prevention or treatment of the related FGIDs ( 21 ). However, according to a study performed by Mantaring et al, probiotics supplementation may not improve infants' gastrointestinal symptoms ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Capozza et al have found some specific probiotics showed a significant reduction in crying and fussing compared to placebo in breastfed infants with colic. Besides, in irritable bowel syndrome (IBS), constipation and gastroesophageal reflux, specific strains of probiotics can improve the related symptoms, although current evidence is insufficient to provide any specific recommendation for the prevention or treatment of the related FGIDs ( 21 ). However, according to a study performed by Mantaring et al, probiotics supplementation may not improve infants' gastrointestinal symptoms ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…About the effect of kefir on FDDs, there is no similar type of study in children with disabilities, due to the fact that the diagnostic criteria and the version of the measurement instrument in Latin American Spanish of the Roma Foundation have been recently updated. However, different studies have suggested or reported the efficacy of the use of probiotics in the treatment of FDD in children, such is the case of IBS, functional dyspepsia, abdominal pain and migraine, mostly in controlled clinical trials using a single strain or combination with prebiotics [ 48 , 49 , 50 , 51 ]. Although studies with multi-probiotic species intervention in children are limited, Guandalini et al [ 50 ] reported the benefits of various combinations of probiotic bacteria, including Bifidobacterium breve , Bifidobacterium longum , Bifidobacterium infantis , Lactobacillus acidophilus , Lactobacillus plantarum , Lactobacillus casei , Lactobacillus bulgaris , and Streptococcus thermophilus (a formulation currently available as Vivomixx in Europe and Visbiome in the US and very similar to the modern kefir formulation), on dyspepsia, IBS, functional abdominal pain, flatulence, bloating, among others.…”
Section: Discussionmentioning
confidence: 99%
“…However, different studies have suggested or reported the efficacy of the use of probiotics in the treatment of FDD in children, such is the case of IBS, functional dyspepsia, abdominal pain and migraine, mostly in controlled clinical trials using a single strain or combination with prebiotics [ 48 , 49 , 50 , 51 ]. Although studies with multi-probiotic species intervention in children are limited, Guandalini et al [ 50 ] reported the benefits of various combinations of probiotic bacteria, including Bifidobacterium breve , Bifidobacterium longum , Bifidobacterium infantis , Lactobacillus acidophilus , Lactobacillus plantarum , Lactobacillus casei , Lactobacillus bulgaris , and Streptococcus thermophilus (a formulation currently available as Vivomixx in Europe and Visbiome in the US and very similar to the modern kefir formulation), on dyspepsia, IBS, functional abdominal pain, flatulence, bloating, among others. Interestingly, our results show that the few cases of dyspepsia, aerophagia, irritable bowel, functional abdominal pain and migraine, as well as several of these FDDs grouped into functional constipation that were diagnosed in children with CP at the beginning of the study, did not appear at the end of the modern kefir treatment, which corroborates that the supplementation with various combinations of probiotic bacteria contributes to the reduction in symptoms of various FDDs.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are essential for maintaining children's GI health, which emphasizes their importance as a mainstay of pediatric therapy. Pain is one of the main symptoms of dysbiosis, and probiotics have shown promise in the management of intestinal pain and inflammation in children [45]. These disorders are commonly encountered in clinical practice.…”
Section: Pediatric Gi Healthmentioning
confidence: 99%